Metodología de gestión de proyectos para la división de infraestructura y proyectos del Banco Popular - Ruiz-Moya, José Vidal (Instituto Tecnológico de Costa Rica, 2015)
The Division of infrastructure projects of Banco Popular has among its main functions to manage the institutional infrastructure projects, manage and administer the institutional maintenance of buildings and lease expiration control contracts for leased premises; directing the efforts of these areas to objectives of the Directorate of Administrative Support and Corporate Strategic Plan. This research proposes a professional project management methodology for the division of infrastructure and projects of the bank, specifically directed to the area of institutional infrastructure projects. To develop the reference framework proposed in project management it is required to make a diagnose of the current situation that Division faces up regarding to maturity in project management, tools, processes, procedures, and skills, to determine the level of project management maturity in the Division. Additionally, it will determine the critical success factors to be taken into account for the development of projects at the DIP. Once completed, the analysis of the level of maturity it will be demonstrated that it does not have a standard methodology for managing institutional infrastructure projects, and lacks of metrics, policies, processes and tools to evaluate the performance of projects, which is adversely affecting the performance of projects. The development of the proposed methodology is based on the PMBOK® (Guide to the Project Management the PMI®) and given that the Bank is an institution of nonstate public law governing, it operates under the rules of public law, these are considered the factors of greatest impact on public sector projects in regards of the government's extension to the PMBOK® Guide. Finally, it concluded that due to the lack of a project management methodology the maturity level of the Division is impacted, making a standard in the activities and tools to make managing projects successful. And it is recommended to implement the proposed methodology in a period not exceeding one year, considering a balanced matrix structure in the Division, such that, allow to keep the management in institutional maintenance and management of institutional projects . Key words: Institutional infrastructure projects, PMI®, PMBok®, maturity in project management, project management, critical success factors, methodology and public institution.
Proyecto de graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2015.
Keywords: Gestión de proyectos; Metodología; Derecho; Instituciones públicas